2021
DOI: 10.1186/s13229-021-00456-4
|View full text |Cite
|
Sign up to set email alerts
|

Neurite orientation dispersion and density imaging reveals white matter microstructural alterations in adults with autism

Abstract: Background Evidences suggesting the association between behavioral anomalies in autism and white matter (WM) microstructural alterations are increasing. Diffusion tensor imaging (DTI) is widely used to infer tissue microstructure. However, due to its lack of specificity, the underlying pathology of reported differences in DTI measures in autism remains poorly understood. Herein, we applied neurite orientation dispersion and density imaging (NODDI) to quantify and define more specific causes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 84 publications
9
29
0
Order By: Relevance
“…On the other hand, MD increases were observed in language‐related tracts in children and adults with ASD. The distinction between FA and MD results in adults was also reported in previous experimental DTI studies (Andica et al, 2021; Catani et al, 2016). These deviations may result from the distinctive trajectories of diffusion parameters with age.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…On the other hand, MD increases were observed in language‐related tracts in children and adults with ASD. The distinction between FA and MD results in adults was also reported in previous experimental DTI studies (Andica et al, 2021; Catani et al, 2016). These deviations may result from the distinctive trajectories of diffusion parameters with age.…”
Section: Discussionsupporting
confidence: 83%
“…Besides, a few studies disposed of the artifacts and head motion in the image acquisition (Kumar et al, 2010; Samson et al, 2016; Thomas et al, 2011). For the ROI tracts, 29 articles investigated the dorsal pathway (AF/SLF) (such as Andica et al, 2021; Kato et al, 2019; Lei et al, 2019), and 17, 13, and 17 studies involved UF, IFOF, and ILF, respectively. For DTI metrics, FA and MD were reported more generally than other parameters (e.g., AD or RD) in the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…, 2020 ( 44 ) Psychogenic nonepileptic seizures NR NR 37/34 a CG a : 39.7 ± 10.9 Pt: 36.7 ± 11.8 CG a : 56.8 Pt: 29.4 3 47, 46 directions b = 1500, 3000 ODI, NDI, FWF VBM WM ↓NDI in the UF, corticospinal tract, and cingulum pathways ↓FWF in the corticospinal tract ICVF in the corticospinal tract and posterior cingulum were negatively correlated with depression FWF in the corticospinal tract was negatively correlated with posttraumatic stress scores Andica et al. , 2021 ( 39 ) ASD Chronic NR 25/26 HC: 34.4 ± 9.0 Pt: 32.9 ± 9.2 HC: 68.0 Pt: 73.1 3 32 directions b = 1000, 2000 NDI, ODI, V iso TBSS, ROI WM ↓NDI in the right hemisphere and anterior left hemisphere ↑V iso in the posterior left hemisphere NDI in the ATR was negatively correlated with communication scores Matsuoka et al. , 2020 ( 38 ) ASD Chronic Mixed 29/28 HC: 27.3 ± 4.9 Pt: 28.9 ± 6.0 HC: 82.8 Pt: 85.7 3 30, 30 directions b = 1000, 2000 NDI, ODI VBM GM ↑ODI in the occipital gyrus ODI was positively correlated with low registration and a passive behavioral response Yasuno et al.…”
Section: Resultsmentioning
confidence: 98%
“…Three studies assessed NODDI indices in patients with autism spectrum disorder ( 37 , 38 , 39 ). One study investigated gray matter microstructure and found increased ODI in the left occipital gyrus.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we focus on two biomarkers: 1) Fractional anisotropy (FA) from the diffusion tensor model, which is arguably the most widely used dMRI biomarker, and 2) Orientation dispersion (OD) from the NODDI model [39], which is a more complex model than diffusion tensor and which has been shown to be a more specific biomarker in some studies [4,29].…”
Section: Atlas Developmentmentioning
confidence: 99%